A three‐dimensional cell culture system as an in vitro canine mammary carcinoma model for the expression of connective tissue modulators. (15th March 2016) - Cardoso, T. C.; Sakamoto, S. S.; Stockmann, D.; Souza, T. F. B.; Ferreira, H. L.; Gameiro, R.; Vieira, F. V.; Louzada, M. J. Q.; Andrade, A. L.; Flores, E. F.
Abstract: In this study, derived complex carcinoma (CC) and simple carcinoma (SC) cell lines were established and cultured under two‐dimensional (2D) and three‐dimensional (3D) conditions. The 3D was performed in six‐well AlgiMatrix™ (LifeTechnologies®, Carlsbad, CA, USA) scaffolds, resulting in spheroids sized 50–125 µm for CC and 175–200 µm for SC. Cell viability was demonstrated up to 14 days for both models. Epidermal growth factor receptor (EGFR) was expressed in CC and SC in both systems. However, higher mRNA and protein levels were observed in SC 2D and 3D systems when compared with CC ( P < 0.005). The connective tissue modulators, metalloproteinases‐1, ‐2, ‐9 and ‐13 (MMPs), relaxin receptors 1 and 2 ( RXR1 and RXR2 ) and E‐cadherin ( CDH1 ) were quantitated. All were upregulated similarly when canine mammary tumour (CMT)‐derived cell lines were cultured under 3D AlgiMatrix, except CDH1 that was downregulated ( P < 0.005). These results are promising towards the used of 3D system to increase a high throughput in vitro canine tumour model.